2013
DOI: 10.3748/wjg.v19.i43.7620
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids in liver diseases

Abstract: Branched chain amino acids (BCAAs) have been shown to affect gene expression, protein metabolism, apoptosis and regeneration of hepatocytes, and insulin resistance. They have also been shown to inhibit the proliferation of liver cancer cells in vitro, and are essential for lymphocyte proliferation and dendritic cell maturation. In patients with advanced chronic liver disease, BCAA concentrations are low, whereas the concentrations of aromatic amino acids such as phenylalanine and tyrosine are high, conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(166 citation statements)
references
References 0 publications
7
156
0
3
Order By: Relevance
“…BCAA catabolic enzymes were markedly reduced in fat tissues of obese persons with metabolic syndrome compared with weight-matched healthy obese subjects. 28 In addition to diabetes, the three BCAAs have been found to be related to CVD, stroke, and liver function, [29][30][31] and these conditions are correlated with diabetes. [32][33][34] These observations underscore the importance of these amino acids in metabolic pathways, and their value in monitoring adverse metabolic changes warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…BCAA catabolic enzymes were markedly reduced in fat tissues of obese persons with metabolic syndrome compared with weight-matched healthy obese subjects. 28 In addition to diabetes, the three BCAAs have been found to be related to CVD, stroke, and liver function, [29][30][31] and these conditions are correlated with diabetes. [32][33][34] These observations underscore the importance of these amino acids in metabolic pathways, and their value in monitoring adverse metabolic changes warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The BCAAs are widely used in clinical treatment, including for the treatment of metabolic stress, hepatic encephalopathy, and chronic renal failure, and the effect and mechanism BCAA treatment has been widely explored [13]. However, few studies have been published on the effect of BCAAs on the function of islet cells.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Several clinical trials have suggested that BCAA supplementation improves the prognosis of cirrhotic patients, and a recent review concludes that their supplementation improves nutritional status and quality of life in patients with advanced cirrhosis, and some international guidelines already recommend their use. 36 Another review of meta-analysis recommends oral administration of BCAAs in hepatic encephalopathy, especially in combination with nonabsorbable disaccharides. 37 In hepatocellular carcinoma BCAAs supplementation improves quality of life and helps preserve liver function during treatment.…”
Section: Malnutrition In Liver Cirrhosismentioning
confidence: 99%